Padrões de diversidade funcional em comunidades de lagartos no sul do Pantanal - Silva, Karoline Rodrigues da (2019)
Seasonal variations have great influence on biotic and abiotic factors and on lizards may be important in changes in activity patterns. Therefore, functional measures can be used to assess the nature and nature of the environment and / or the effects of ecosystems, one of which is flooding. Our objective was to evaluate the functional diversity patterns of lizard communities under flood disturbance in the Pantanal of Nhecolândia - MT. For this we focus on differences in functional richness and functional equitability between the dry season and the rainy season considering three functional characteristics of the lizards. To capture the lizards were used sets of fall traps with guide fences. We recorded 782 lizards of 13 species, 12 genera and nine families. The number of species and abundance were similar between drought and flood. The most abundant species were Ameivula ocellifera with 439 individuals and Vanzosaura rubricauda with 249 individuals, totaling 87% of the total recorded individuals. The richness and functional equitability were similar to the two seasons presenting random pattern. Our results may be related to the unpredictability of seasonal fluctuations, together with the different degrees of disturbance that the Pantanal has suffered, does not allow a clear organization of the community.